'Human beings in the round': Towards a general theory of the human sciences. (July 2014) - Gabriel, Norman; Kaspersen, Lars Bo
In this introduction we highlight Norbert Elias's bold attempt to build a general model of the human sciences, integrating the social and natural sciences. We point to a range of different disciplines, emphasizing how he rarely developed a consistent critique of individual disciplines, though he often made some very fruitful suggestions about they should be reconceptualized in a relational and more integrative way. Based on our own research on survival units and the contributions to this special issue, we discuss the innovative potential of his ambition for transdisciplinary research, while at the same time offering an overview of some of the limitations in his theoretical perspective. We reassess his attempt to integrate the natural and social sciences within one universal testable model, and, at the same time, we consider areas like religion and economics that were rarely systematically investigated in his own theoretical approach.